Dilutions of Apis mellifera Improve Metabolic Abnormalities Induced by Antiretroviral Therapy in Mice - Recco, M. L.; Bornia, L. B.; Jr, T. Sakurada; Jr, M. Spack; Pupulin, A. R. T. (Highlights on Medicine and Medical Research Vol. 6, 2021)
Background: Highly Active Antiretroviral Therapy (HAART) is associated with significant mortality decreased and risk in AIDS progression. However, complications due to long-standing HIV infection and treatment have become increasingly important. Complications include hepatic and nephrotoxic effects of HAART. Studies on honeybee (Apis mellifera) venom proved its anticancer effects, antimicrobial activity, immunomodulatory and vasoconstrictor effects. Current study evaluates the effect of dilutions of Apis mellifera on metabolic alterations induced in mice subjected to antiretroviral therapy (HAART). Material and Methods: Each experimental group comprised 10 animals: (I) animals treated with HAART diluted in 1.2 mL water gavage/day, (II) animals treated with HAART diluted in 1.2 mL water gavage/day + Apis mellifera diluted 1x1012 in water 1.0 mL once daily added to the drinking water (1:10 mL) available ad libitum, (III) animals treated with HAART diluted in 1.2 mL water gavage/day + Apis mellifera diluted 1x1060 in water 1.0 mL once daily added to the drinking water (1:10 mL) available ad libitum, (IV) untreated (control group) received 1.2 mL water by gavage/day. The experimental groups were treated for 15 days. Clinical evaluation (body weight, water intake and ration, excretion products, behavior) was performed before and after treatment and the serum cholesterol, triglycerides; hepatic enzymes (AST, ALT) and creatinine were assessed by specific methods. Results were analyzed with Graph Pad Prism using Student´s t test. Results:. Animals treated with HAART and Apis mellifera diluted (II and III) had higher body weight gain, lower levels of triglycerides (20%), cholesterol (20%) and creatinine (50%) when compared to animals treated with antiretroviral therapy. Conclusion: Our studies demonstrate that Apis mellifica extract used in diluted form has beneficial effects for animals treated with antiretroviral therapy. There is an improvement in the levels of cholesterol, triglycerides, liver enzymes and renal profile. Apis mellifera diluted 1x1012 and 1x1060 showed a significant effect on creatinine levels when compared to HAART group and demonstrated possible effect on kidney injury.